THE EFFECTS OF ERROR TREATMENT ON INTERLANGUAGE: A CASE STUDY OF INDONESIAN LEARNERS LEARNING ENGLISH AS A FOREIGN LANGUAGE - Fauziati, Endang (Universitas Muhammadiyah Surakarta, 2010)
This study investigates the effects of a short-term error treatment (ET) on ILerrors, with specific attention to the learnersâ ungrammatical items. The problemstates âwhat are the effects of a ET on the learnersâ ungrammatical items?â, Aretheir ungrammatical items fossilized (in a sense that they are static in nature) ordynamic after the learners have been exposed to the ET. The data were the learnersâ free compositions collected four times: prior and after the ET and two monthsÂ afterwards. They were analyzed quantitatively and qualitatively. The result indicates that the ET changed the state of the learnersâ ungrammatical items. Theybecame so dynamic. At a certain period, some appeared; then due to the ET, someÂ were destabilized, some were fluctuating, and others were still stabilized. New errors appeared as they started learning to use new grammatical items. The conclusion drawn from this study is that ET can change the state of the learnersâ ILerrors; ET contributes to the destabilization process. Errors may persist momentarily but they can be destabilized. The ET still works on the learners who are atÂ their post puberty. Thus, there is a great possibility for the learners to acquire complete TL grammar since their ungrammatical items are dynamic.Key words: error treatment, interlanguage, fossilized, stabilization.